RAPID SURVEY OF GASTRICAL SYMPTOMS IN THE STUDENTS OF THE FACULTY OF PUBLIC HEALTH, UNIVERSITAS MUHAMMADIYAH JAKARTA IN 2022 - Mhuthia Adila, Amira; Fauziah, Munaya; Febrianti, Thresya; Surury, Istianah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Gastritis is one of the non-communicable diseases which is a public health problem. According to data from the Indonesian Ministry of Health (2018), the incidence of gastritis in Indonesia is 40.8%. South Tangerang recorded as many as 8,432 (10.43 percent) people reported experiencing gastritis symptom syndrome; this makes gastritis one of the ten most common diseases in South Tangerang. This study aimed to determine the association between sex, frequency of eating, mealtime, frequency of irritating eating and stress with gastritis symptoms. The method used in this study is a rapid survey of 210 samples determined through two-stage cluster sampling and then tested univariately and bivariate using Chi-Square with α=0.05. The results showed that there was no association between sex (p-value = 0.087) and mealtime (p-value = 0.273) with gastritis recurrence. There is a relationship between eating frequency (p-value = 0.009), risk eating frequency (p-value = 0.000), and stress (p-value = 0.000) with gastritis symptoms. This study concludes that the factors associated with gastritis symptoms include the frequency of eating, the frequency of eating irrittation and stressful. Meanwhile, gender and meal times were not associated with gastritis symptoms. Suggestions that for teenagers to pay attention to the frequency of eating, reduce the frequency of eating irritating and do meditation and strengthen faith in order to avoid stress that can trigger gastritis symptoms.